2023
DOI: 10.26466/opusjsr.1207071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Teleworking and Strategic Orientations on Resilience in the Post-Pandemic Period

Abstract: This study investigates the effects of the strategic orientations of SMEs, which are in the group most affected by the COVID-19 pandemic process, which exemplifies volatility, uncertainty, complexity, and ambiguity (VUCA) conditions, on their organizational resilience, and the differentiation of SMEs organizational resilience according to the teleworking style they prefer. The research model and hypotheses were examined by using the Structural Equation Modeling technique on the data collected by the survey met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The strongest support for the work attributes dimension and the business strategy sub-dimension, which stand out as the factors with the highest impact on telework in our findings, was given by research results of Yorulmaz et al [67]. In the research they conducted in the service sector, the effects of telework types on resilience were investigated, and based on the results of the research; it was suggested that the company adopt regular telework models as a business strategy.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The strongest support for the work attributes dimension and the business strategy sub-dimension, which stand out as the factors with the highest impact on telework in our findings, was given by research results of Yorulmaz et al [67]. In the research they conducted in the service sector, the effects of telework types on resilience were investigated, and based on the results of the research; it was suggested that the company adopt regular telework models as a business strategy.…”
Section: Discussionmentioning
confidence: 52%
“…Each company implements telework in various ways that will suit itself and its business model. A wide range of application types is encountered, from working entirely from home to working remotely in exceptional cases [67].…”
Section: Teleworkmentioning
confidence: 99%
See 2 more Smart Citations